Power System Performance Improvement by Optimal Placement and Sizing of SVC using Genetic Algorithm - Prasanth Duraisamy; Arul Ponnusamy (International Journal of Applied Power Engineering (IJAPE), 2017)
The power system loss minimization becomes more important as the need of power generation is more recent days. The loss minimization improves the voltage profile which improves the loadability of the system. In many types of flexible AC transmission system (FACTS) devices static var compensators (SVC) are cost vise it is affordable and it improves the system performance with lesser size. Here SVC is optimally placed in a test system of 30 bus system. Genetic algorithm is used to find the optimal results.